Investigating the Dynamic Soil Behaviour of Cape Flat Sands Under Earthquake Cyclic Loading - Otim, Gerald (Department of Civil Engineering, 2024)
Most geotechnical structures are surrounded by partially or unsaturated soils, which can greatly affect their dynamic properties, such as shear modulus and damping ratio. Therefore, this necessitates an inclusive methodology to consider and incorporate the degree of saturation in seismic analyses to ensure that seismic designs are not overly conservative based on local soil conditions. In Cape Town, South Africa, limited soil characterization on cyclic testing has been executed on Cape Flat Sands, although the area is in a sensitive seismic region of magnitude ML 6.1 - 7.5. As a result, geotechnical engineers may be using dynamic correlations that are too conservative due to limited assumptions about soil type, earthquake response, relative density, plasticity, confining pressure, and saturation level. The cyclic properties of the Cape Flat Sands were evaluated at ten different cyclic axial strains (0.005%, 0.01%, 0.02%, 0.05%, 0.1%, 0.2%, 0.4%, 0.6%, 0.8% and 1.0%), three relative densities (loose dense, medium dense, and dense), and five saturation levels (0%, 25%, 50%, 75% and 100%). The tests were conducted using cyclic triaxial equipment, and soil classification tests were performed according to the latest standards of the American Society for Testing Materials (ASTM). The Unified Soil Classification System classified the Cape Flat Sands as poorly graded sand. The results of the undrained cyclic triaxial tests, which measured shear modulus, damping ratio, and excess pore pressure ratio, are also included. Based on the results, correlations were developed to determine the relationship between the damping ratio and normalized shear modulus. Additionally, the applicability of existing dynamic models was evaluated by superimposing them on the test data for shear modulus, damping ratio, and excess pore pressure ratio. To identify the factors and their interactions that affected the values of the shear modulus, damping ratio, and excess pore pressure ratio, MANOVA was conducted. Repeatability and quality control of results was carried out to ensure that the results were precise and reproducible using the same test standard and operator. A ground response and free vibration analysis of a five-storied building were executed using ProShake software and Plaxis 2D software. This was achieved using the normalized shear modulus and damping ratio with shear strain curves against a soil profile obtained along the R300 road within the Cape Flats region. A water table underlay this soil profile at 2.45m depth, enabling varying saturation states to be adopted. The Nahanni (1985)-RSN497 ground motion from the PEER NGA ground database was adapted for dynamic analysis. The results of the ground response analysis, free vibration and earthquake analysis showed that the different saturation states, relative density, and equivalent dynamic properties influenced the behavior of the ground motion parameters for each respective sandy layer. This study has provided invaluable insights into the dynamic properties of Cape Flat Sands under earthquake cyclic loading and it has also highlighted specific areas that require further research to enhance its understanding.